Adult T-Cell Leukemia/Lymphoma in a Caucasian Patient After Sexual Transmission of Human T-Cell Lymphotropic Virus Type 1. (6th March 2015) - Sibon, David; Cassar, Olivier; Duga, Isabelle; Brouzes, Chantal; Ghez, David; Pasquier, Christophe; Sibon, Claire; Desrames, Alexandra; Mortreux, Franck; Wattel, Eric; Bazarbachi, Ali; Gessain, Antoine; et al.
Abstract: Adult T-cell leukemia/lymphoma (ATLL), a T-cell neoplasm caused by human T-cell lymphotropic virus type 1 (HTLV-1), develops in the majority of cases in individuals who were infected with HTLV-1 as young children, by their mother during prolonged breastfeeding. We report the case of a Caucasian French man, whose parents were HTLV-1-seronegative and who developed ATLL after HTLV-1 sexual transmission by a Cameroonian woman. This hypothesis was corroborated by genotyping of the patient's virus, which revealed an HTLV-1B strain, found only in Central Africa, especially in Cameroon. Thus, ATLL may develop after HTLV-1 infection during adulthood, outside breastfeeding.